High-performance work system practices in Vietnam: a study of managers' perceptions. Issue 3 (20th September 2019) - Do, Hoa; Budhwar, Pawan; Patel, Charmi
Abstract : Purpose: The purpose of this paper is to explore the effects of high-performance work systems (HPWS) on the performance of Vietnamese firms. It teases out the antecedents and effects of managers' beliefs about why HPWS exist and are adopted within their firms, and also what effects HPWS practices have on their firm's performance. Design/methodology/approach: The authors adopt a longitudinal design to provide insights into why and how HPWS are shaped and diffused, and also how they convert the inputs into outputs such as HR outcomes, firm innovation and performance, based on a sample of 17 in-depth interviewees who were CEOs, HR managers, general managers in 17 Vietnamese service firms. Findings: Results demonstrate that HPWS can impact both employee outcomes (e.g. employee attitudes, behaviours and productivity), and firm performance (e.g. firm innovation, firm growth and profit growth). Practical implications: The study underscores the importance of HPWS as a response to organizational change that can help deal with external pressures and provides evidence about how the HPWS-innovation relationship is established in the research context. Originality/value: This is among the first study to extend some aspects of institutional theory to understand the context of how and why HPWS are shaped and executed to respond to environmental pressures. It underscores the importance of HPWS as a response to organizational change that can help deal with external pressures, thereby serving as a leading step to yield meaningful outcomes with respect to the advancement of this research stream.